Nieporadne jeszcze dźwięki. O materialności dziennika Rutki Laskier - Jasińska, Anita (Narracje o Zagładzie [czasopismo zamknięte], 2017)
Still Inept Sounds. On the Materiality of Rutka Laskier’s Diary The author of the article endeavours to present the history of the diary of Rut “Rutka” Laskier, a Jew from Będzin, who died in Auschwitz II–Birkenau. Laskier, called the Polish Anne Frank, wrote her diary for several months in an inconsistent and irregular manner. The notebook survived the war, but the information about its discovery reached the local media in as late as 2006. Jasińska analyses the Notebook, carefully examining the issues discussed by the girl, the topics chosen by her, and the pieces of information – either described or meticulously omitted – directly concerning Christian and/or Jewish culture and tradition. The author of the article pays a lot of attention to the “materiality” of the diary, as Paweł Rodak names it. She describes the material, the medium, the writing tools, and the girl’s handwriting. Such a way of looking at the diary makes it possible to broaden the cognitive perspective and to provide interesting interpretations. Jasińska also examines the very publication of the diary and the changes accompanying it on the proofreading‑editing level. She wonders whether and how it influences the act of reading the text, the social reception of the diary entries, and the assessment and value of Rutka’s Notebook as a historical source. Key words: Będzin, diary, Holocaust, evidence, publication